Supporting Preschool Pre-Reading Development through Illustrated Flashcards and Chain Word Play: A Quasi-Experimental Study in Indonesian Kindergartens - Leonia, Rizqy Aisyah; Khotimah, Nurul; Rachman, Budi; Fairuzillah, Muhammad Naufal (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Pre-reading development plays an important role in children’s early literacy formation, yet questions remain over how different instructional routes support this process in preschool settings. Although visual media and language-based play are both widely used in early childhood classrooms, comparative evidence on their relative contribution to early literacy remains limited, particularly in everyday kindergarten contexts. This study examined the effects of illustrated flashcards and chain word play on the pre-reading skills of children aged 5 to 6 years and compared their relative performance under classroom conditions. A quantitative quasi-experimental design was employed using a non-equivalent group pretest-posttest structure. The participants were 60 kindergarten children from two early childhood education institutions in Yogyakarta, Indonesia, with 30 children in each intervention group. Pre-reading skills were assessed through an observation-based and performance-based instrument covering letter recognition, initial sound identification, word recognition, and simple word reading. Data were analysed using paired-sample and independent-sample t-tests after normality and homogeneity assumptions were satisfied. Both interventions were associated with statistically significant gains in children’s pre-reading scores. However, the posttest comparison showed a significant difference between groups, with the illustrated flashcard group achieving stronger end-point performance. These findings suggest that visual-symbolic support may offer a more immediate advantage for early pre-reading development, while chain word play remains valuable for strengthening the oral and phonological foundations of literacy. The study contributes comparative evidence to current discussions on emergent literacy by showing that different instructional forms may not produce the same pattern of gain, even when both are pedagogically worthwhile.